Resource-based strategy for enhancing village-owned enterprise competitive advantage: Impact of capabilities and networks - Roni Kambara; Wawan Ichwanudin; Hayati Nupus; Asas Worasutr (Universitas Ahmad Dahlan, 2025)
Village-owned enterprise have faced increasing challenges in improving their competitiveness in a rapidly evolving market environment. Effective resource management and good governance practices are seen as key factors that could drive competitive advantage, while supply chain flexibility and strong business networks are essential for village-owned enterprise to adapt to changing market conditions. This study aims to examine the relationship between resource management capabilities, good governance excellence, supply chain flexibility, and business network acceptability in relation to competitive advantage levels in village-owned enterprise in Indonesia. Using a quantitative approach with a survey design, data was collected through an online survey of 120 village-owned enterprise managers who had worked for at least 1 years. Data analysis was conducted using partial least squares and structural equation modeling. The results show that resource management capabilities and Good Governance Excellence do not have a significant direct effect on competitive advantage levels. However, business network acceptability plays a mediating role that strengthens the relationship between resource management capabilities and increased competitiveness. This study provides practical implications that effective resource management and strong business networks can enhance company competitiveness. Further research is recommended to broaden the scope by involving other sectors to test this model.